KONTROL DIRI SEBAGAI VARIABEL MODERATOR PADA PENGARUH STRES TERHADAP INTENSITAS MEROKOK MAHASISWA - Nurfitriany Fakhri; Muhammad Nur Auliah Baso Rewa; Basti Tetteng; Sahril Buchori (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: Smoking is something that students do, especially when they are stressed. People's stress levels have been linked to more intense smoking. Objective: to ascertain the function of self-control as a moderating factor in the impact of stress on smoking intensity among college students. Method: The present investigation employs quantitative methodologies. The study sample consisted of 224 students residing in Makassar City who reported smoking. Result: The findings of the initial hypothesis examination indicated that the observed p-value was 0.035 (p < 0.05), and the correlation coefficient was 0.631. The obtained R-square score of 0.443 suggests that stress accounts for 44.3% of the variance in smoking intensity and exerts a statistically significant positive influence on it. The findings from the second hypothesis test utilizing MRA analysis indicated an interaction value of -0.015. Conclusion: The interaction value shows a negative value, which means that the higher the self-control, the smaller the influence of stress on smoking intensity, and vice versa. The results of this research can be used by universities, counselors, and therapists who are involved in the intervention process to reduce and stop smoking addiction so that they can develop intervention programs that emphasize the importance of increasing students' self-control.